2021
DOI: 10.1177/23337214211039974
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 Lockdown on Health and Psychosocial Functioning in Older Adults Aged 70 and Over

Abstract: The COVID-19 pandemic led to a state-imposed lockdown in the UK; there are many psychosocial consequences of pandemics, with older adults potentially at an increased risk. The current study assessed psychosocial functioning in a sample of older adults in the UK with baseline data collected pre-lockdown and follow-up 12 weeks later during lockdown. Thus, allowing investigation of the effect of COVID-19 and associated lockdown on psychosocial well-being. Thirty-five older adults (Mean age = 76.06, sex = 12 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
1
8
0
6
Order By: Relevance
“…A study with individuals aged 70 and older showed that in this age group lockdown led to a significant worsening of perceived stress, well-being, depressive symptoms, mood disturbance and memory. On the other hand, significant improvements in self-reported physical health symptoms, social interaction, time spent engaging in physical activity and certain aspects of relationship quality were demonstrated [ 62 ]. Follow-up showed that well-being, depression and mood were still negatively affected post-lockdown [ 62 ].…”
Section: Covid-19 and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study with individuals aged 70 and older showed that in this age group lockdown led to a significant worsening of perceived stress, well-being, depressive symptoms, mood disturbance and memory. On the other hand, significant improvements in self-reported physical health symptoms, social interaction, time spent engaging in physical activity and certain aspects of relationship quality were demonstrated [ 62 ]. Follow-up showed that well-being, depression and mood were still negatively affected post-lockdown [ 62 ].…”
Section: Covid-19 and Depressionmentioning
confidence: 99%
“…On the other hand, significant improvements in self-reported physical health symptoms, social interaction, time spent engaging in physical activity and certain aspects of relationship quality were demonstrated [ 62 ]. Follow-up showed that well-being, depression and mood were still negatively affected post-lockdown [ 62 ].…”
Section: Covid-19 and Depressionmentioning
confidence: 99%
“…Eine Studie mit Personen ab 70 Jahren zeigte, dass in dieser Altersgruppe der Lockdown zu einer signifikanten Verschlechterung des wahrgenommenen Stresses, des Wohlbefindens, der depressiven Symptome, der Stimmungsstörungen und des Gedächtnisses führte. Andererseits wurden signifikante Verbesserungen der selbst berichteten körperlichen Gesundheitssymptome, der sozialen Interaktion, der Zeit, die mit körperlicher Aktivität verbracht wurde, und bestimmter Aspekte der Beziehungsqualität nachgewiesen [50]. Die Nachuntersuchung zeigte, dass Wohlbefinden, Depression und Stimmung auch nach dem Lockdown noch negativ beeinflusst wurden [50].…”
Section: Covid-19 Und Depressionunclassified
“…Andererseits wurden signifikante Verbesserungen der selbst berichteten körperlichen Gesundheitssymptome, der sozialen Interaktion, der Zeit, die mit körperlicher Aktivität verbracht wurde, und bestimmter Aspekte der Beziehungsqualität nachgewiesen [50]. Die Nachuntersuchung zeigte, dass Wohlbefinden, Depression und Stimmung auch nach dem Lockdown noch negativ beeinflusst wurden [50]. Psychische Gesundheitsprobleme, die sich während der Pandemie manifestierten, waren überwiegend mit der aktuellen Einsamkeit und der präpandemischen Belastung verbunden [48].…”
Section: Covid-19 Und Depressionunclassified
“…Pirasath & Sundaresan (2021) sebagai ancaman yang vital bagi kesehatan masyarakat diseluruh dunia. Hipertensi tidak terkontrol, dan berisiko menimbulkan komplikasi lebih lanjut pada pasien tersebut seperti stroke, Acute Coroner Syindrome (ACS), gagal jantung, gagal ginjal (Docherty et al, 2021;Pirasath & Sundaresan, 2021). Adapun salah satu faktor risiko penderita hipertensi yang bisa mengalami tekanan darah yang tidak terkontrol adalah kurangnya aktivitas fisik (Kurnia et al, 2020).…”
Section: Pendahuluanunclassified